A STUDY OF TOTAL QUALITY MANAGEMENT PRACTICE APPROACHES FOR SMALL BUSINESSES IN INDONESIA - fawwaz althoof varaby; ida bagus putu aditya (IULI Publisher, 2022)
The focus of this study is on TQM adoption in small enterprises, particularly in Indonesia. The main data that will be studied in this paper is taken from the paper that discusses how warung tegal and warung padang implement TQM in their business. The reason the subject is sampled as the main data is because the subjects are sufficient to represent SMEs in the food industry in Indonesia. Customer Orientation, Continuous Improvement, and Employee Empowerment are the three components of TQM that are employed as study indicators. The findings reveal that the TQM concept has not been properly applied at Warung Tegal and Warung Padang. This is owing to the fact that not all criteria can be implemented adequately in practice. Consumer orientation is critical since the customer defines quality. To create adjustments, it is necessary to collect information on what the client wants on a frequent basis. In terms of continuous improvement criteria, the average response revealed that the majority of food stalls failed to meet the TQM application in continuous improvement criterion. In terms of employee empowerment, a third of Warung Tegal and Warung Padang employees are recruited from families, which may or may not have anything to do with quality.Keywords: Small businesses entreprises, total quality management, Indonesia